SIGNIFICANCE OF HOUSE DUST MITES IN ATOPIC ALLERGIC PROCESSES - Мусина, Марина Ивановна; Климов, Владимир Васильевич; Загрешенко, Денис Сергеевич; Кухарев, Ярослав Викторович; Шкатова, Алина Николаевна; Пестова, Вера Владимировна; Климов, Андрей Владимирович; Слезкин, Михаил Игоревич; Володина, Мария Александровна; Акобян, Вануш Агабекович; Овчаренко, Екатерина Вадимовна (Medicine in Kuzbass, 2024)
The article has a hybrid nature and includes a review of the modern references on a role of house dust mites in the etiopathogenesis of atopic allergic diseases and original studies of dust accumulation in different rooms (bedrooms, kitchens, student hostels) in three districts of Tomsk with an assessment of the impact on allergic rhinitis patients living in some of these rooms. Materials and methods. 30 rooms in student hostels, apartments and kitchens in three districts of Tomsk were examined. Samples of house dust were collected and the dust density was calculated (the mass of dust per unit volume of the room). Among the residents of these rooms, 24 patients with allergic rhinitis, of both sexes, were identified at the average age of 20.4 ± 0.47 years. Results. In all samples, the dust density exceeded the sanitary norm by 1.85-3.6 times. This figure was especially high in dormitory rooms and in the kitchens of city apartments. A correlation of average strength between dust density and the presence of perennial allergic rhinitis (r = 0.35) was revealed. Conclusions. Dustiness studies of the rooms showed a significant excess of dust density over sanitary standards in all samples. Among the residents of the studied rooms, patients with allergic rhinitis, one of the atopic diseases, were identified. This confirmes a role of Dermatophagoides mites as major components of house dust hold in atopy etiopathogenesis.